A Chronological History of the Development of the Campus School of Wisconsin State University at La Crosse, 1871-1970 (Seminar paper) - Seielstad, Mary Emmert (My University, 1970)
The study was concerned with the development of the Campus School of the Wisconsin State University at La Crosse, from 1871 to 1970. It was the purpose of this study to: (1) describe the establishment of the Campus School; (2) explain the function and philosophy of the Campus School; (3) recount some of the challenges that were met in building a new school; (4) describe some changes made in the curriculum through the years; (5) describe a few of the extra-curricular activities; and (6) describe events at the time of writing this paper concerning the possible closing of the school. Information for this paper was gathered from both primary and secondary sources. The primary source materials included unpublished papers of the late Emery W. Leamer, director of the school from 1925 to 1952; an interview with Alice Drake, a member of the college faculty from 1931 to 1932; interviews with Elmer Lysaker, Margaret Linfeld Annett, and Barbara Emmert Tyznik, former pupils in the Campus School; and unpublished copies of the health program established in the Campus School. Other sources included copies of the La Crosse Tribune, bulletins and catalogues of Wisconsin State University at La Crosse, and clippings from various sources which were available in the La Crosse Public Library and the archives of the Murphy Library of WSU at La Crosse. The director of the Campus School, Richard E. Rasmussen, allowed the researcher to examine copies of annual reports and other papers in his files. The laboratory schools have been an integral part of the teacher-training institutions since the first normal school was built in the United States in 1823. The Campus School of the Wisconsin State University at La Crosse was established in conjunction with the college in 1909, and was located on the first floor of the one college building. The primary purpose for its establishment, as stated in 1909, was to educate children. Its other purposes were to serve as a model school and to give student teachers a place to observe teaching demonstrations, as well as an opportunity to teach. The philosophy of the Campus School was to develop happy, well-adjusted children.
Keywords: Laboratory schools -- Wisconsin -- La Crosse -- History; Wisconsin State University (La Crosse). Campus School -- History